In situ localization and tissue distribution of ostreid herpesvirus 1 proteins in infected Pacific oyster, Crassostrea gigas - Martenot, Claire; Segarra, Amelie; Baillon, Laury; Faury, Nicole; Houssin, Maryline; Renault, Tristan (Journal of Invertebrate Pathology, 2016)
Immunohistochemistry (IHC) assays were conducted on paraffin sections from experimentally infected spat and unchallenged spat produced in hatchery to determine the tissue distribution of three viral proteins within the Pacific oyster, Crassostrea gigas. Polyclonal antibodies were produced from recombinant proteins corresponding to two putative membrane proteins and one putative apoptosis inhibitor encoded by ORF 25, 72, and 87, respectively. Results were then compared to those obtained by in situ hybridization performed on the same individuals, and showed a substantial agreement according to Landis and Koch numeric scale. Positive signals were mainly observed in connective tissue of gills, mantle, adductor muscle, heart, digestive gland, labial palps, and gonads of infected spat. Positive signals were also reported in digestive epithelia. However, few positive signals were also observed in healthy appearing oysters (unchallenged spat) and could be due to virus persistence after a primary infection. Cellular localization of staining seemed to be linked to the function of the viral protein targeted. A nucleus staining was preferentially observed with antibodies targeting the putative apoptosis inhibitor protein whereas a cytoplasmic localization was obtained using antibodies recognizing putative membrane proteins. The detection of viral proteins was often associated with histopathological changes previously reported during OsHV-1 infection by histology and transmission electron microscopy. Within the 6h after viral suspension injection, positive signals were almost at the maximal level with the three antibodies and all studied organs appeared infected at 28h post viral injection. Connective tissue appeared to be a privileged site for OsHV-1 replication even if positive signals were observed in the epithelium cells of different organs which may be interpreted as a hypothetical portal of entry or release for the virus. IHC constitutes a suited method for analyzing the early infection stages of OsHV-1 infection and a ...